The impact of stratospheric aerosol injection: a regional case study - Cohen, Sabrina L.; Hurrell, James W.; Lombardozzi, Danica L. (Frontiers in Climate, 2025)
Stratospheric aerosol injection (SAI) is a form of climate intervention that has been proposed to limit future warming and mitigate some of the adverse impacts of climate change while humanity continues efforts to reduce emissions and atmospheric concentrations of greenhouse gases. In this study, we use an Earth system model to compare the projected effects of a climate change scenario to three different SAI scenarios. Our analysis centers on both climate and crop productivity impacts. We focus on four Global South regions: South Asia, East Asia, South Central America, and West Africa. These regions were selected due to their socioeconomic vulnerability to climate change. The SAI scenarios project reduced temperature extremes and greater wet season precipitation, soil moisture and crop productivity compared to the climate change scenario over all four regions. We also find that the extent to which SAI mitigates crop productivity declines due to climate change is likely greater in South Central America and West Africa than in South and East Asia. Our study is a step toward addressing the need for more regional analyses of the potential impacts of different SAI scenarios.